This time it was different? The salience of the Spitzenkandidaten system among European parties. Issue 5 (3rd September 2018) - Braun, Daniela; Popa, Sebastian A.
Abstract: The Lisbon Treaty (2009) introduced key institutional changes to increase the relevance of elections to the European Parliament (EP). Among others, major political groups nominated different lead candidates, the so-called Spitzenkandidaten, for the 2014 EP elections. The aim of this article is to investigate how national political parties react to this new institutional setting. Using data from the 2014 Euromanifesto study, the article examines if and under what conditions political parties put emphasis on the Spitzenkandidaten system in their party manifestos and whether they take positive or negative stances when talking about it. The findings reveal that parties put little emphasis on the issue. Moreover, the factors promoting the Spitzenkandidaten system suggest that parties decide strategically upon emphasising that topic or take a positive stance on it if they expect to benefit from this.